The Effect of Corporate Governance on the Profitability of Non-Financial Companies - Widyaningsih, Rina Wahyu; Ninava, Wiwin Aprelia; Hersugondo (LifeSciFi, 2024)
This study aims to examine the impact of corporate governance (CG) on the profitability of non-financial companies listed on the Indonesia Stock Exchange, with Debt-to-Equity Ratio (DER) as a moderating variable and Firm Age, Market to Book Value (MBV), and ownership structure as control variables. In the context of increasingly competitive business environments, the quality of corporate governance becomes crucial for achieving sustainable performance. This research utilizes company data from 2020 to 2023 and employs regression analysis to test the proposed hypotheses. The findings are expected to provide insights into the importance of good governance, optimal capital structure, and ownership structure in enhancing profitability, as well as offering practical implications for managers and investors in decision-making processes.